The culture of the Seven Years' War : empire, identity, and the arts in the eighteenth-century Atlantic world - De Bruyn, Frans; Regan, Shaun, 1970- (University of Toronto Press, 2014)
With essays by notable scholars that address the war's impact in Europe and the Atlantic world, this volume is sure to become essential reading for those interested in the relationship between war, culture, and the arts.